Body mass index as a prognostic factor in patients with extranodal natural killer/T-cell lymphoma, nasal type - Liu, Jie (Oncotarget, 2016)
Epidemiological evidence has shown that body mass index (BMI) can predict survival in several types of cancer. However, the role of BMI in extranodal natural killer/T-cell lymphoma, nasal type (ENKTL) is still unclear. This retrospective single-center study included 251 newly diagnosed patients to determine the prognostic value of BMI in ENKTL. Of these, 203 patients received chemoradiotherapy, 37 received chemotherapy alone, 8 received radiotherapy alone, and 3 received only best supportive care. With a median follow-up of 28 months, the estimated 3-year overall survival (OS) and progression-free survival (PFS) rates were 64.4% and 60.9%, respectively. The receiver-operating characteristic curve showed that 20.8 kg/m(2) was the optimal cut-off of BMI to predict survival. BMI < 20.8 kg/m(2) was associated with lower 3-year OS (52.8% vs. 72.9%, P = 0.001) and PFS (48.8% vs. 69.8%, P < 0.001) rates. Multivariate analysis indicated that BMI, performance status, lactate dehydrogenase (LDH) levels, chemotherapy, and radiotherapy were independent prognostic factors for OS. Furthermore, BMI, number of extranodal sites, performance status, LDH, and radiotherapy were predictive of PFS. These results suggest that BMI at the cut-off of 20.8 kg/m(2) might be a prognostic factor in patients with ENKTL.